Method for in-situ raman spectroscopy characterization of adsorption characteristics of bimetallic catalyst intermediates

CN122961971APending Publication Date: 2026-10-23ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611374654.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本申请提供了一种原位拉曼光谱表征双金属催化剂中间体吸附特征的方法,解决了现有技术中依赖跨样品对照方式无法在同一双金属样品内部实现协同界面位点与单一金属位点吸附信号解耦的技术问题;提高了对双金属催化剂表面协同界面位点吸附*OCHO中间体这一贡献程度的定量表征准确性

Benefits of technology

[0007]本申请提供的技术方案中,通过构建铜位点原子簇模型及铜铋协同位点原子簇模型并对二者分别进行天然铜同位素质量及富集铜同位素质量下的双频振动计算得到铜位点理论位移量及协同位点理论位移量,使理论位移量的来源建立在振动本征值方程求解结果之上,而非依赖跨样品对照方式间接推断,从而使后续位移比率解析所依据的判据基准与协同界面位点的电子结构耦合机理直接关联;通过以天然铜盐溶液及富集铜同位素盐溶液分别作为电沉积液制备天然同位素树枝状双金属电极及富集同位素树枝状双金属电极,使二者在化学组成、晶体结构及局部配位环境上保持一致,仅原子核质量存在差异,将此前需要依赖多变量对照样品间接推断的信号归属问题,转化为同一双金属样品内部的单变量比较问题,使配对特征峰组的实测峰位差值能够真实反映铜原子在对应振动模式本征矢量中的位移分量占比,而不掺杂样品批次或结构差异带来的干扰成分;通过将配对特征峰组中每一配对特征峰的实测峰位差值分别与铜位点理论位移量及协同位点理论位移量进行比值解析得到铜位点位移比率及协同位点位移比率,并由此划分得到铜位点特征峰、铜铋协同位点特征峰及候选铋位点特征峰,使叠加谱图中原本相互重叠的位点信号能够依据各自振动本征矢量中金属原子位移分量的差异被逐一区分,弥补了现有技术仅依据固定峰位比对或经验排除法进行信号归属、缺乏机制性支撑的不足。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122961971A_ABST
    Figure CN122961971A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of spectral detection, and discloses a method for in-situ Raman spectrum characterization of adsorption characteristics of a bimetallic catalyst intermediate. The method comprises the following steps: constructing a site model by using copper-bismuth atomic clusters and calculating the theoretical displacement amount of double-frequency vibration under natural and enriched copper isotopes; preparing natural and enriched isotope bimetallic electrodes and collecting Raman spectra of OCHO intermediate at the same potential under the reaction condition of electrocatalytic carbon dioxide reduction to formic acid, and obtaining a paired characteristic peak group through peak pairing; analyzing the displacement ratio of the ratio of the actual peak site difference value to the theoretical displacement amount, and dividing the characteristic peaks of copper sites, copper-bismuth cooperative sites and candidate bismuth sites according to the displacement ratio; verifying the characteristic peaks of bismuth sites by combining under-potential stripping voltammetry data, calculating the peak area proportion of copper-bismuth cooperative sites, and obtaining the adsorption contribution proportion-potential curve. The application improves the quantitative characterization accuracy of the contribution degree of the adsorption of the OCHO intermediate on the surface cooperative interface sites of the bimetallic catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of spectroscopic detection technology, and in particular to a method for in-situ Raman spectroscopy characterizing the adsorption characteristics of bimetallic catalyst intermediates. Background Technology

[0002] Electrocatalytic reduction of carbon dioxide to formic acid is a promising carbon neutralization pathway. Bimetallic catalysts have been extensively studied due to their high conductivity and suitable intermediate adsorption energies, with the copper-bismuth bimetallic system being a typical example. To elucidate the reaction mechanism of bimetallic catalysts, existing techniques typically employ in-situ Raman spectroscopy, acquiring characteristic Raman signals from the catalyst surface in real time during the electrocatalytic reaction. By monitoring the intensity and shift changes of the characteristic peak corresponding to the *OCHO intermediate, the degree of adsorption of this intermediate on the catalyst surface is determined, thus aiding in the analysis of the reaction pathway and selectivity mechanism. Some existing works further introduce peak-splitting fitting techniques, splitting the overlapping signals in the superimposed spectrum into several sub-peaks and assigning them based on the comparison of peak positions with known literature values ​​or theoretical calculations, or using the slope of the vibrational characteristic peak position changing with electrode potential as a criterion for distinguishing different site microenvironments.

[0003] However, bimetallic catalyst surfaces typically contain both single metal sites and bimetallic synergistic interface sites, both of which can adsorb the same *OCHO intermediate. Furthermore, the Raman signals generated by these sites are spatially superimposed. Existing peak fitting and shift slope criteria are based on cross-sample comparisons, i.e., by preparing single-metal control samples or gradient samples with different metal ratios, testing their overall Raman signals separately, and then making a lateral comparison. The essential flaw of this comparison method is that, in addition to the different metal compositions, the crystal structure, local coordination environment, and electronic structure state of the control sample and the test bimetallic sample also change, resulting in multivariate differences. This means that the criteria established based on such control samples cannot truly decouple the contributions of the synergistic interface site signals and the single metal site signals in the superimposed spectra, nor can they eliminate the systematic bias caused by the structural differences between the control sample and the test sample to the criteria itself.

[0004] Since cross-sample comparison methods cannot achieve univariate decoupling of site signals within the same sample, existing technologies further rely on fixed peak position comparison or empirical exclusion methods to determine signal attribution. Such criteria lack independent physical mechanism support and can only provide qualitative or semi-quantitative attribution results. Because criteria lacking mechanistic support cannot distinguish whether the shift or intensity change of a certain sub-peak originates from the electronic structure coupling of the bimetallic synergistic interface or from sample batch differences or fluctuations in testing conditions, existing technologies further cannot obtain direct experimental evidence of signal attribution within the same bimetallic sample, while maintaining complete consistency in chemical composition and crystal structure, by changing only a controllable single physical variable. As a result, the quantitative characterization of the specific contribution of the adsorption of the *OCHO intermediate at the bimetallic synergistic interface site remains at the level of indirect inference relying on multivariate control samples. Summary of the Invention

[0005] This application provides a method for in-situ Raman spectroscopy characterizing the adsorption features of intermediates in bimetallic catalysts, which solves the technical problem in the prior art that the adsorption signals of synergistic interface sites and single metal sites cannot be decoupled within the same bimetallic sample by relying on cross-sample control methods; and improves the quantitative characterization accuracy of the contribution of synergistic interface sites on the surface of bimetallic catalysts to the adsorption of *OCHO intermediates.

[0006] This application provides a method for in-situ Raman spectroscopy characterizing the adsorption characteristics of bimetallic catalyst intermediates, the method comprising: Using copper and bismuth atomic clusters as the matrix, copper site atomic cluster models and copper-bismuth cooperative site atomic cluster models are constructed. The copper site atomic cluster models and the copper-bismuth cooperative site atomic cluster models are subjected to dual-frequency vibration calculations under natural copper isotope mass and enriched copper isotope mass, respectively, to obtain the theoretical displacement of copper sites and the theoretical displacement of cooperative sites. A two-step electrodeposition process was performed using a natural copper salt solution and a copper-enriched isotope salt solution as electrodeposition solutions to obtain a natural isotope dendritic bimetallic electrode and an enriched isotope dendritic bimetallic electrode. The natural isotope dendritic bimetallic electrode and the enriched isotope dendritic bimetallic electrode were placed at multiple potential test points within a preset potential range, and under the reaction conditions that the two electrodes were at the same potential at each potential test point, in-situ Raman spectroscopy was performed. The obtained Raman spectra were then divided and the peaks were paired to obtain paired characteristic peak groups. The measured peak position difference of each paired characteristic peak in the paired characteristic peak group is analyzed by ratioing it to the theoretical displacement of the copper site and the theoretical displacement of the cooperating site, respectively, to obtain the copper site displacement ratio and the cooperating site displacement ratio; the copper site characteristic peak, the copper-bismuth cooperating site characteristic peak and the candidate bismuth site characteristic peak are obtained by dividing the copper site characteristic peak, the copper-bismuth cooperating site characteristic peak and the candidate bismuth site characteristic peak by the copper site displacement ratio and the cooperating site displacement ratio. The natural isotope dendritic bimetallic electrode was subjected to underpotential deposition stripping voltammetry to obtain underpotential stripping voltammetric data. The correlation between the characteristic peaks of the candidate bismuth sites and the underpotential stripping voltammetric data was verified to obtain the characteristic peaks of the bismuth sites. The peak area ratio of the characteristic peaks of the copper-bismuth synergistic sites was calculated at each potential test point to obtain the adsorption contribution ratio-potential curve.

[0007] The technical solution provided in this application constructs a copper site cluster model and a copper-bismuth co-located site cluster model, and performs dual-frequency vibration calculations on both models under natural copper isotope mass and enriched copper isotope mass respectively to obtain the theoretical displacement of the copper site and the theoretical displacement of the co-located site. This establishes the source of the theoretical displacement based on the solution of the vibrational eigenvalue equation, rather than relying on indirect inference through cross-sample comparisons. This directly links the criterion used for subsequent displacement ratio analysis to the electronic structure coupling mechanism of the co-located interface site. Furthermore, by using natural copper salt solution and enriched copper isotope salt solution as electrodeposition solutions to prepare natural isotope dendritic bimetallic electrodes and enriched isotope dendritic bimetallic electrodes respectively, the two electrodes maintain consistency in chemical composition, crystal structure, and local coordination environment, differing only in atomic nucleus mass. This eliminates the previous reliance on indirect inference through multivariate comparison samples. The problem of signal attribution is transformed into a univariate comparison problem within the same bimetallic sample. This allows the measured peak position difference of paired characteristic peak groups to truly reflect the proportion of the displacement component of copper atoms in the eigenvector of the corresponding vibration mode, without interference from sample batches or structural differences. By analyzing the ratio of the measured peak position difference of each paired characteristic peak in the paired characteristic peak group to the theoretical displacement of copper sites and the theoretical displacement of cooperating sites, the displacement ratio of copper sites and the displacement ratio of cooperating sites are obtained. Based on this, characteristic peaks of copper sites, characteristic peaks of copper-bismuth cooperating sites, and characteristic peaks of candidate bismuth sites are obtained. This allows the site signals that were originally overlapping in the superimposed spectrum to be distinguished one by one according to the difference in the displacement component of metal atoms in their respective vibration eigenvectors. This makes up for the shortcomings of existing technologies that only rely on fixed peak position comparison or empirical exclusion methods for signal attribution and lack mechanistic support. Attached Figure Description

[0008] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0009] Figure 1 This is a thermogram showing the current fluctuation amplitude distribution under the combined gradient screening of copper sulfate and sulfuric acid concentrations in the electrodeposition solution in the embodiments of this application. Figure 2This is a schematic diagram comparing the original superimposed Raman spectrum with the peak fitting results of three types of sub-peaks: copper site, copper-bismuth co-occurrence site, and bismuth site, in the embodiments of this application. Detailed Implementation

[0010] This application provides a method for in-situ Raman spectroscopy characterization of the adsorption features of a bimetallic catalyst intermediate. The terms "first," "second," "third," "fourth," etc. (if present) in the specification, claims, and accompanying drawings of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data used can be interchanged where appropriate so that the embodiments described herein can be implemented in a sequence other than that illustrated or described herein. Furthermore, the terms "comprising" or "having" and any variations thereof are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.

[0011] For ease of understanding, the specific process of the embodiments of this application is described below. One embodiment of the method for in-situ Raman spectroscopy characterization of the adsorption characteristics of bimetallic catalyst intermediates in this application includes: Using copper and bismuth atomic clusters as the matrix, copper site atomic cluster models and copper-bismuth cooperative site atomic cluster models were constructed. Dual-frequency vibration calculations were performed on the copper site atomic cluster models and the copper-bismuth cooperative site atomic cluster models under the natural copper isotope mass and the enriched copper isotope mass, respectively, to obtain the theoretical displacement of copper sites and the theoretical displacement of cooperative sites. Specifically, using copper and bismuth atom clusters as the matrix, copper-site atom cluster models and copper-bismuth cooperative site atom cluster models were constructed. The arrangement, interatomic spacing, and coordination number of metal atoms in the copper and bismuth atom clusters were assigned values ​​based on the copper phase lattice constant and bismuth phase lattice constant obtained from X-ray diffraction characterization, and the interface coordination number and interatomic spacing obtained from high-resolution transmission electron microscopy characterization. The number of copper atoms in the copper-site atom cluster model was set to 16, and the total number of copper and bismuth atoms in the copper-bismuth cooperative site atom cluster model was set to 14. This number was based on the first and second coordination shell atoms in the measured coordination environment covering the dendritic bimetallic electrode. Density functional theory vibrational frequencies were calculated for both the copper-site atom cluster model and the copper-bismuth cooperative site atom cluster model. The exchange-correlated functional was the generalized gradient approximation functional, the basis set was a plane wave basis set, and the cutoff energy was set to 400 electron volts. This cutoff energy value was determined based on the convergence test of the calculated cutoff energy change. Dual-frequency vibration calculations refer to assigning the same atomic cluster model a natural copper isotope mass of 63.55 atomic mass units and an enriched copper isotope mass of 64.93 atomic mass units, respectively, while keeping the atomic coordinates, exchange correlation functionals, and basis sets unchanged. The vibrational eigenvalue equations are then solved separately to obtain two sets of characteristic peak frequency values. The theoretical displacement of the copper site is the result of subtracting the characteristic peak frequency values ​​obtained under the natural copper isotope mass from those obtained under the enriched copper isotope mass for the copper site atomic cluster model. The theoretical displacement of the cooperating site is obtained for the copper-bismuth cooperating site atomic cluster model in the same manner.

[0012] Two-step electrodeposition was performed using natural copper salt solution and copper isotope-enriched salt solution as electrodeposition solutions to obtain natural isotope dendritic bimetallic electrodes and enriched isotope dendritic bimetallic electrodes. The natural isotope dendritic bimetallic electrodes and enriched isotope dendritic bimetallic electrodes were used for the electrocatalytic reduction of carbon dioxide to formic acid reaction. In-situ Raman spectra of the *OCHO intermediate were collected at multiple potential test points within a preset potential range, and under the reaction conditions that the two electrodes were at the same potential at each potential test point, the Raman spectra were divided and the peaks were paired to obtain paired characteristic peak groups. Specifically, a natural copper salt solution and a copper isotope-enriched salt solution were used as electrodeposition solutions. Electrodeposition was performed for 600 seconds at a current density of 5 mA / cm² and a temperature of 25°C to obtain a dendritic copper framework. The dendritic copper framework was then placed in a bismuth nitrate solution and electrodeposited for 600 seconds at a current density of 2 mA / cm² to obtain a natural isotope dendritic bimetallic electrode and a copper isotope-enriched dendritic bimetallic electrode. The current density and duration of the two electrodeposition steps were determined based on the confirmation by scanning electron microscopy that the bismuth completely coated the surface of the copper framework. The natural isotope dendritic bimetallic electrode and the copper isotope-enriched dendritic bimetallic electrode were used for the electrocatalytic reduction of carbon dioxide to formic acid. The preset potential range was -0.6 volts to -1.2 volts. Compared to the reversible hydrogen electrode, the potential test points were spaced 0.1 volts apart. This potential range was determined based on the formate formation initiation potential and current density plateau range obtained from linear scan voltammetry. In-situ Raman spectra of the *OCHO intermediate were acquired under the same reaction conditions at each potential test point. The obtained Raman spectra were divided into several sub-peaks using Gaussian functions in the wavenumber ranges of 1280 to 1320 and 1420 to 1460, respectively, to obtain the peak position and peak area values ​​of each sub-peak. The sub-peaks obtained by the natural isotope dendritic bimetallic electrode and the sub-peaks obtained by the enriched isotope dendritic bimetallic electrode were compared one by one. Two sub-peaks with a peak position difference in the wavenumber range of 0 to 3 and a peak area ratio difference of no more than 10 percentage points in the corresponding wavenumber range were identified as a pair of peaks. The pairing results at all potential test points were summarized to obtain the paired characteristic peak group. The upper limit of the peak position difference of 3 wavenumbers was determined based on the upper limit of the theoretical displacement of the copper site, and the upper limit of the peak area ratio difference of 10 percentage points was determined based on the peak area measurement error range corresponding to the Raman spectrum signal-to-noise ratio.

[0013] The measured peak position difference of each paired characteristic peak in the paired characteristic peak group is analyzed by ratioing it to the theoretical displacement of the copper site and the theoretical displacement of the cooperating site, respectively, to obtain the copper site displacement ratio and the cooperating site displacement ratio; the copper site characteristic peak, the copper-bismuth cooperating site characteristic peak and the candidate bismuth site characteristic peak are obtained by dividing the copper site characteristic peak, the copper-bismuth cooperating site characteristic peak and the candidate bismuth site characteristic peak based on the copper site displacement ratio and the cooperating site displacement ratio. Specifically, the measured peak position difference of each paired characteristic peak in the paired characteristic peak group, that is, the result of subtracting the peak position value of the corresponding sub-peak obtained by the enriched isotope dendritic bimetallic electrode from the peak position value of the sub-peak obtained by the natural isotope dendritic bimetallic electrode, is divided by the theoretical displacement of the copper site and the theoretical displacement of the cooperating site, respectively, to obtain the copper site displacement ratio and the cooperating site displacement ratio. Paired characteristic peaks with a copper site shift ratio of not less than 0.85 were classified as copper site characteristic peaks. This 0.85 value was determined based on the deviation range between the theoretical and measured shift values ​​obtained after verification of the copper site atom cluster model, which is 3 times the actual displacement value. Paired characteristic peaks with a copper site shift ratio less than 0.85 and a co-location shift ratio of not less than 0.85 were classified as copper-bismuth co-location characteristic peaks. Paired characteristic peaks with both a copper site shift ratio and a co-location shift ratio not greater than 0.15 were classified as candidate bismuth site characteristic peaks. The reason for marking them as candidates is that bismuth has only one stable isotope, bismuth 209, and it is not possible to directly verify the bismuth site characteristic peaks by isotope substitution. They need to be transferred to subsequent steps to complete the confirmation with electrochemical data independent of the Raman spectroscopy itself.

[0014] Underpotential deposition stripping voltammetry was performed on a natural isotope dendritic bimetallic electrode to obtain underpotential stripping voltammetric data. The correlation between the characteristic peaks of candidate bismuth sites and the underpotential stripping voltammetric data was verified to obtain the characteristic peaks of bismuth sites. The peak area ratio of the characteristic peaks of copper-bismuth synergistic sites at each potential test point was calculated to obtain the adsorption contribution ratio-potential curve of copper-bismuth synergistic sites for *OCHO intermediate.

[0015] Specifically, underpotential deposition stripping voltammetry was performed on a natural isotope dendritic bimetallic electrode at the same potential test points as the electrocatalytic reduction of carbon dioxide to formic acid reaction. The amount of bismuth dissolved on the electrode surface at each potential test point was obtained by integrating the charge of the oxidation peak corresponding to bismuth in the stripping voltammetry curve. This value characterizes the density of surface active sites of bismuth at the corresponding potential. The sum of the dissolution charge values ​​at each potential test point yielded the underpotential stripping voltammetry data. The peak area values ​​of candidate bismuth site characteristic peaks at each potential test point were compared with the dissolution charge values ​​at the corresponding potential test points in the underpotential stripping voltammetry data using Pearson correlation coefficient calculations. Candidate bismuth site characteristic peaks with a correlation coefficient not less than 0.8 were classified as bismuth site characteristic peaks. The value of 0.8 was determined based on the lower limit of correlation coefficient, which is generally considered to be a strong correlation in Pearson correlation statistics. Divide the peak area of ​​the characteristic peak of the copper-bismuth synergistic site by the sum of the peak areas of the characteristic peaks of the copper site, the copper-bismuth synergistic site, and the bismuth site at the same potential test point to obtain the adsorption contribution ratio of the copper-bismuth synergistic site for the *OCHO intermediate at that potential test point. Sort and connect the adsorption contribution ratios of all potential test points according to the potential value to obtain the adsorption contribution ratio-potential curve of the copper-bismuth synergistic site for the *OCHO intermediate.

[0016] In one specific embodiment, the construction of both the copper site cluster model and the copper-bismuth co-located site cluster model is based on the following: the copper phase lattice constant and bismuth phase lattice constant obtained by X-ray diffraction characterization of the natural isotope dendritic bimetallic electrode; and the interface coordination number and interfacial interatomic spacing obtained by high-resolution transmission electron microscopy characterization of the copper-bismuth interface region of the natural isotope dendritic bimetallic electrode. A pure copper verification electrode is obtained by electrodeposition using a natural copper salt solution alone. The pure copper verification electrode is then subjected to in-situ Raman spectroscopy of the *OCHO intermediate under the same reaction conditions as the electrocatalytic reduction of carbon dioxide to formic acid, obtaining the characteristic peak positions of the pure copper verification electrode. The simulated Raman characteristic peak positions of the *OCHO intermediate obtained after structural optimization of the copper site cluster model are compared with the characteristic peak positions of the pure copper verification electrode; the difference between the two is no more than [value missing]. Yes, the copper site atom cluster model is confirmed to be effective.

[0017] Specifically, the construction of the copper site cluster model and the copper-bismuth co-located site cluster model are based on the following: the copper phase lattice constant of 0.3615 nm and the bismuth phase lattice constant of 0.4746 nm obtained by X-ray diffraction characterization of the natural isotope dendritic bimetallic electrode. These two values ​​are obtained by substituting the diffraction angle values ​​of the copper phase 111 crystal plane and the bismuth phase 012 crystal plane in the X-ray diffraction pattern into the Bragg equation for back calculation; and the interface coordination number of 8 and the interatomic spacing of 0.271 nm obtained by high-resolution transmission electron microscopy characterization of the copper-bismuth interface region of the natural isotope dendritic bimetallic electrode. These two values ​​are obtained by the measured calibration of the atomic row spacing at the copper-bismuth interface in the high-resolution transmission electron microscopy image. A pure copper verification electrode was obtained by electrodeposition using a natural copper salt solution alone. The electrodeposition current density was 5 mA / cm², the temperature was 25°C, and the duration was 600 seconds. These three values ​​were determined through the following screening process: five gradient points were selected within the current density range of 1 to 10 mA / cm², three gradient points within the temperature range of 20 to 30°C, and five gradient points within the duration range of 300 to 900 seconds. After electrodeposition, the dendritic branch morphology of each combination was observed using a scanning electron microscope. Combinations with a standard deviation to mean of the dendritic branch spacing not exceeding 0.1 and without branch aggregation or collapse were selected, corresponding to a current density of 5 mA / cm², a temperature of 25°C, and a duration of 600 seconds. The pure copper verification electrode was placed under the same reaction conditions as the electrocatalytic reduction of carbon dioxide to formic acid reaction, and in-situ Raman spectroscopy of the *OCHO intermediate was performed to obtain the peak positions of the characteristic peaks of the pure copper verification electrode.

[0018] The copper site atom cluster model was substituted into the aforementioned exchange-correlation functional and basis set for structure optimization. The optimization convergence criterion was set to an atomic force value less than 0.02 eV / Å. This criterion value was determined through the following tests: Four gradients of the convergence criterion (0.05, 0.03, 0.02, and 0.01 eV / Å) were used for structure optimization, and the corresponding characteristic peak frequencies of the *OCHO intermediate were calculated. The frequency differences obtained from adjacent gradients were compared. When the convergence criterion was tightened from 0.03 to 0.02 eV / Å, the frequency difference was less than... The convergence was determined, so a value of 0.02 electron volts per angstrom was chosen. The simulated Raman characteristic peak position of the *OCHO intermediate obtained after structural optimization was compared with the characteristic peak position of the pure copper verification electrode; the difference between the two was no more than [value missing]. Yes, the copper site atom cluster model is confirmed to be effective; This upper limit was determined through the following comparison: The calculated vibrational frequencies of the bismuth-oxygen bond stretching vibration modes obtained from the aforementioned vibrational frequency calculations on the pure bismuth site cluster model were compared with the measured frequencies of the bismuth-oxygen bond stretching vibration modes reported in existing published literature. The difference was [value missing]. This difference reflects the level of systematic deviation between the frequencies calculated by density functional theory and the measured frequencies under the current computational method system. Rounded up This is determined as the upper limit for difference judgment.

[0019] In one specific embodiment, the number of metal atoms in both the copper site cluster model and the copper-bismuth co-located site cluster model is not less than 12; in the dual-frequency vibration calculation, the mass of the natural copper isotope is 63.55 atomic mass units, and the mass of the enriched copper isotope is 64.93 atomic mass units; the theoretical displacement of the copper site and the theoretical displacement of the co-located site are both not less than 3 times the spectral resolution of the spectrometer used for in-situ Raman spectroscopy acquisition, and the theoretical displacement of the co-located site is less than the theoretical displacement of the copper site.

[0020] Specifically, the number of metal atoms in both the copper site cluster model and the copper-bismuth co-located site cluster model is 16. This value was determined through the following tests: Copper site cluster models with 8, 12, 16, and 20 metal atoms were constructed respectively, and vibrational frequencies were calculated. The differences in the characteristic peak frequencies of the *OCHO intermediate obtained under the gradient of adjacent atomic numbers were compared. When the number of atoms increased from 12 to 16, the frequency difference was less than [a certain value]. The convergence has been determined, and when the number of atoms continues to increase to 20, the frequency difference is still less than [a certain value]. To balance computational convergence and computational time, 16 values ​​were selected. In the dual-frequency vibration calculation, the mass of the natural copper isotope was taken as 63.55 atomic mass units, corresponding to the average atomic mass of a mixture of 63-copper and 65-copper at natural abundances of 69.15 mol% and 30.85 mol% respectively. The mass of the enriched copper isotope was taken as 64.93 atomic mass units, corresponding to the average mass of copper atoms in the enriched precursor with a 65-copper isotope purity of 99 mol% or higher. This purity value is consistent with the specifications of commercially available enriched copper salt raw materials. The spectral resolution of the spectrometer used for in-situ Raman spectroscopy was taken as... The theoretical displacement of the copper site and the theoretical displacement of the cooperative site are both not less than three times this value. The factor of 3 was determined through the following test: Raman spectra of the same *OCHO intermediate characteristic peak were repeatedly acquired 10 times and peak fitting was performed. The standard deviation of the obtained peak position values ​​was [value missing]. The standard deviation is related to the spectral resolution value. For values ​​within the same order of magnitude, three times the spectral resolution value is taken as the lower limit of the theoretical displacement, ensuring that the ratio of the theoretical displacement to the random error in peak position determination is not less than 3, thus guaranteeing the validity of the displacement ratio calculation results. The relationship that the theoretical displacement of the cooperating site is less than that of the copper site is derived from the calculation result that the proportion of the copper atom displacement component in the vibrational eigenvector of the copper-bismuth cooperating site atomic cluster model is less than that of the copper site atomic cluster model. In the copper-bismuth cooperating site atomic cluster model, the copper atom displacement component is distributed because bismuth atoms participate in the vibrational mode, thus reducing the frequency shift amplitude caused by the mass substitution of enriched copper isotopes. This relationship is a direct output of the dual-frequency vibration calculation results and is not a pre-set condition.

[0021] In one specific embodiment, the two-step electrodeposition includes using copper foam as a conductive substrate, performing a first-step electrodeposition in a natural copper salt solution or a copper-enriched isotope salt solution to obtain a dendritic copper framework, and then placing the dendritic copper framework in a bismuth nitrate solution for a second-step electrodeposition to obtain a natural isotope dendritic bimetallic electrode or an isotope-enriched dendritic bimetallic electrode.

[0022] Specifically, using copper foam as a conductive substrate, the first step of electrodeposition was performed in an electrodeposition solution with a copper sulfate concentration of 0.1 mol / L and a sulfuric acid concentration of 0.5 mol / L. The current density was 5 mA / cm², the temperature was 25°C, and the duration was 600 seconds. These current density, temperature, and duration values ​​are consistent with the aforementioned screening results for dendritic copper skeletons, and will not be repeated. The copper sulfate concentration of 0.1 mol / L was determined through the following screening process: five gradient points were selected within the range of 0.05 to 0.3 mol / L for electrodeposition, and the branch density and current efficiency of the copper skeleton obtained at each gradient point were measured. The gradient point with a current efficiency of not less than 90% and the highest branch density was selected, corresponding to a concentration of 0.1 mol / L. The sulfuric acid concentration of 0.5 mol / L was determined through the following screening process: four gradient points were selected within the range of 0.1 to 1 mol / L, and the current fluctuation amplitude during the electrodeposition process at each gradient point was measured. The gradient point with a current fluctuation amplitude of no more than 5% was selected, corresponding to a concentration of 0.5 mol / L. The natural copper salt solution and the copper-enriched isotope salt solution were respectively subjected to the first step of electrodeposition according to the above parameters. The two were prepared in parallel to obtain a natural isotope dendritic copper framework and an enriched isotope dendritic copper framework, respectively. The morphological equivalence of the two was confirmed by the aforementioned three characterization results: scanning electron microscopy, X-ray photoelectron spectroscopy and high-resolution transmission electron microscopy.

[0023] The natural isotope dendritic copper framework and the enriched isotope dendritic copper framework were then placed in an electrodeposition solution with a bismuth nitrate concentration of 0.02 mol / L for a second electrodeposition step. The current density was set at 2 mA / cm² and the duration was set at 600 seconds. The determination of the duration of 600 seconds was consistent with the aforementioned bismuth element coverage screening results, and the derivation was not repeated. The bismuth nitrate concentration of 0.02 mol / L was determined through the following screening process: Five gradient points were selected within the range of 0.005 to 0.05 mol / L. The bismuth-copper atomic ratio on the electrode surface after 600 seconds of the second electrodeposition at each gradient point was measured. Gradient points with a bismuth-copper atomic ratio reaching 95% coverage and no bismuth particle agglomeration were selected, corresponding to a concentration of 0.02 mol / L. The current density of 2 mA / cm² was determined through the following screening process: Five gradient points were selected within the range of 1 to 5 mA / cm². The degree of filling of the dendritic branch gaps by the bismuth deposition layer at each gradient point was measured. Gradient points with a bismuth deposition layer that did not block the branch gaps and a bismuth-copper atomic ratio reaching 95% coverage were selected, corresponding to a current density of 2 mA / cm². The first step of electrodeposition uses a branch made from a natural copper salt solution as raw material, which, when combined with the second step of electrodeposition, yields a natural isotope dendritic bimetallic electrode. The second step of electrodeposition uses a branch made from a copper isotope-enriched salt solution as raw material, which, when combined with the second step of electrodeposition, yields an isotope-enriched dendritic bimetallic electrode. Both are prepared in parallel using their respective independent raw material branches and must be completely preserved for subsequent in-situ Raman spectroscopy acquisition and comparison at the same potential.

[0024] Figure 1 This is a heatmap showing the current fluctuation amplitude distribution under the gradient screening of copper sulfate and sulfuric acid concentrations in the electrodeposition solution in this embodiment of the application. The horizontal axis represents the copper sulfate concentration gradient value, and the vertical axis represents the sulfuric acid concentration gradient value. The value marked in each square in the figure is the percentage value of the measured current fluctuation amplitude during the electrodeposition process under the corresponding concentration combination condition. The color depth corresponds to the current fluctuation amplitude value shown by the color scale on the right. This figure shows that the current fluctuation amplitude reaches a minimum of 2.1% under the condition of copper sulfate concentration of 0.10 mol / L and sulfuric acid concentration of 0.50 mol / L. Based on this, the specific implementation parameters of the electrodeposition solution are determined to be this concentration combination.

[0025] In one specific embodiment, the natural isotope dendritic bimetallic electrode and the isotope-enriched dendritic bimetallic electrode were characterized by scanning electron microscopy, X-ray photoelectron spectroscopy and high-resolution transmission electron microscopy. The difference in the spacing between the dendritic branches was no more than 5%, the difference in the surface bismuth-copper atomic ratio was no more than 3%, and the difference in the local interatomic spacing at the copper-bismuth interface was no more than 1%.

[0026] Specifically, scanning electron microscopy was used to characterize both the natural isotope dendritic bimetallic electrode and the enriched isotope dendritic bimetallic electrode. Ten dendritic branches were randomly selected on the surface of each electrode, and the distance between adjacent branches at each branch was measured and averaged. The average distance obtained from the natural isotope dendritic bimetallic electrode was subtracted from the average distance obtained from the enriched isotope dendritic bimetallic electrode, and the ratio of this difference to the average distance obtained from the natural isotope dendritic bimetallic electrode was taken. This ratio should not exceed 5%. The 5% value was determined by the following test: the above distance measurement was repeated for three groups of natural isotope dendritic bimetallic electrodes prepared by electrodeposition in the same batch. The maximum fluctuation range of the obtained ratio was 4.6%. The fluctuation range was rounded up to 5%, which was used as the upper limit of the difference for judging the morphological equivalence between electrodes. X-ray photoelectron spectroscopy was used to characterize the natural isotope dendritic bimetallic electrode and the enriched isotope dendritic bimetallic electrode, respectively. The atomic ratio of bismuth to copper on the surface of the two electrodes was determined. The difference between the two atomic ratios was determined as the percentage difference to the atomic ratio of the natural isotope dendritic bimetallic electrode. This percentage difference did not exceed 3%. The value of 3% was determined by rounding down the maximum fluctuation range of 3.1% for repeated measurements of the same batch of electrodes. High-resolution transmission electron microscopy (HRTEM) was used to characterize the copper-bismuth interface regions of both the natural isotope dendritic bimetallic electrode and the isotope-enriched dendritic bimetallic electrode. Five copper-bismuth atomic columns were randomly selected from the interface region of each electrode for interatomic spacing calibration. The average value was calculated, and the ratio of the difference between the two average values ​​to the average local interatomic spacing at the interface of the natural isotope dendritic bimetallic electrode was determined as the percentage difference. This percentage difference was not to exceed 1%, and the 1% value was determined by rounding down to the maximum fluctuation range of 0.9% for repeated calibration of the same batch of electrodes. The measured average local interatomic spacing at the interface of the natural isotope dendritic bimetallic electrode corresponding to this percentage difference was 0.271 nm, consistent with the interatomic spacing of 0.271 nm assigned during the construction of the copper-bismuth cooperating site atomic cluster model. This confirms that the measured value can be directly used for model construction.

[0027] In one specific embodiment, the method further includes electrodeposition of a natural copper salt solution and a copper-enriched isotope salt solution separately to obtain a natural isotope control copper electrode and a copper-enriched isotope control copper electrode, wherein the difference in electrodeposition current efficiency and the difference in dendritic branch density between the two electrodes do not exceed 5%.

[0028] Specifically, electrodeposition was performed separately using natural copper salt solution and copper-enriched isotope salt solution, with a current density of 5 mA / cm², a temperature of 25°C, and a duration of 600 seconds. These parameters were consistent with those for the aforementioned electrodeposition of dendritic copper frameworks, resulting in natural and enriched isotope control copper electrodes. The electrodeposition current efficiency was calculated by dividing the measured mass of the electrodeposited copper layer by the product of the applied charge and the electrochemical equivalent of copper. The current efficiency value obtained from the natural and enriched isotope control copper electrodes was subtracted from the current efficiency value obtained from the natural isotope control copper electrode, and the ratio of this difference to the current efficiency value of the natural isotope control copper electrode was determined as the percentage difference in current efficiency. The dendritic branch density was obtained by counting the number of branches per unit area in the scanning electron microscope image, and the percentage difference in branch density between the natural and enriched isotope control copper electrodes was calculated in the same manner. The percentage difference in current efficiency and the percentage difference in dendritic branch density both do not exceed 5%. The 5% value was determined by rounding down the maximum fluctuation of 4.3% obtained from repeated measurements of current efficiency and branch density of three groups of natural isotope control copper electrodes prepared by electrodeposition in the same batch. This value and the aforementioned upper limit of 5% for the difference in dendritic branch spacing are values ​​obtained from two independent measurement processes and are not cited from the same source.

[0029] In one specific embodiment, the preset potential range is -0.6 volts to -1.2 volts, relative to the reversible hydrogen electrode; the reaction conditions for the electrocatalytic reduction of carbon dioxide to formic acid are a potassium bicarbonate solution saturated with carbon dioxide; the in-situ Raman spectrum of the *OCHO intermediate is collected at 1280 nm. to Wavenumber window and to Performed within the wavenumber window.

[0030] Peak segmentation was performed using a Gaussian function for multi-component fitting; peak pairing was based on the peak position difference being within a certain range. to The pairing condition is that the difference between the area ratio of the interval and the peak area does not exceed 10 percentage points.

[0031] Specifically, the preset potential range was -0.6 volts to -1.2 volts. This range, relative to the reversible hydrogen electrode, was determined by the following measurements: Linear scanning voltammetry was performed on a natural isotope dendritic bimetallic electrode. The reduction current corresponding to formate formation showed a significant increase at -0.6 volts, and the current density plateaued at -1.2 volts. Therefore, this range was chosen to cover the period from the initial potential of formate formation to the current density plateau. The reaction conditions for the electrocatalytic reduction of carbon dioxide to formic acid were a carbon dioxide-saturated potassium bicarbonate solution at a concentration of 0.1 mol / L. This concentration was determined by measuring the electrolyte conductivity and formate Faraday efficiency at five gradient points within the range of 0.05 to 0.5 mol / L, and the gradient points corresponding to these points achieved optimal levels of both conductivity and Faraday efficiency were selected. *The in-situ Raman spectroscopy acquisition window for the OCHO intermediate was set to 1280°. to and to Two wavenumber windows were determined after performing the aforementioned vibrational frequency calculations on the pure bismuth site cluster model and the copper site cluster model. The calculation results show that the characteristic frequencies of the carbon-oxygen asymmetric stretching vibration mode and the carbon-hydrogen bending vibration mode corresponding to the *OCHO intermediate fall within the range of the two windows mentioned above.

[0032] The obtained raw Raman spectra were fitted with a Gaussian function within the two wavenumber windows mentioned above. The initial peak position was taken as the wavenumber value corresponding to the maximum intensity of the raw spectrum within the wavenumber window, and the initial half-width was taken as... The least squares method is used to minimize the sum of squared residuals between the fitted curve and the original spectral intensity values, thus obtaining the peak position, peak intensity, and peak area values ​​of each sub-peak. Spectral peak pairing is based on the peak position difference being within a certain range. to An interval is one of the pairing conditions; the upper limit of this interval is... The upper limit of the theoretical displacement value of the copper site is taken, and the theoretical displacement value of the copper site itself is not less than the spectral resolution value of the spectrometer. 3 times Take the integer value of the lower limit. The upper limit of the peak position difference is the minimum possible value that the pairing conditions cover the theoretical displacement of the copper site. The second pairing condition is that the difference in peak area ratio does not exceed 10 percentage points. This value is determined by rounding up to more than three times the standard deviation of 2.6 percentage points obtained from 10 repeated measurements of the peak area ratio of the same sub-peak. The 10 percentage point value is used to ensure that the pairing conditions have a sufficient tolerance range for random measurement errors.

[0033] Figure 2This is a schematic diagram comparing the original superimposed Raman spectrum with the peak fitting results of three types of sub-peaks: copper site, copper-bismuth co-occurrence site, and bismuth site, as shown in the embodiments of this application. The solid line represents the natural isotope dendritic bimetallic electrode at 1280°. to Wavenumber window and to The original superimposed Raman spectrum acquired within the wavenumber window. The dashed line, dotted line, and dotted line are the sub-peak fitting curves of the copper site characteristic peak, the copper-bismuth co-occurrence site characteristic peak, and the bismuth site characteristic peak obtained after multi-component fitting with Gaussian function, respectively. The vertical axis is the normalized Raman intensity value, and the horizontal axis is the Raman shift value. This figure intuitively shows the specific results of the superimposed spectrum being decomposed into three types of sub-peaks with different peak positions and shapes after peak splitting processing within two characteristic peak windows.

[0034] In one specific embodiment, copper site shift ratios of not less than 0.85 are classified as copper site characteristic peaks; copper site shift ratios of less than 0.85 and co-location shift ratios of not less than 0.85 are classified as copper-bismuth co-location characteristic peaks; copper site shift ratios of not more than 0.15 and co-location shift ratios of not more than 0.15 are classified as candidate bismuth site characteristic peaks; and if the correlation coefficient obtained from correlation verification is not less than 0.8, the corresponding candidate bismuth site characteristic peaks are classified as bismuth site characteristic peaks.

[0035] Specifically, paired characteristic peaks with a copper site displacement ratio of not less than 0.85 are classified as copper site characteristic peaks. This value of 0.85 was determined as follows: Ten repeated isotope peak alignment measurements were performed on a pure copper verification electrode. The standard deviation of the ratio of the measured displacement to the theoretical displacement of the copper site was 0.05. The theoretical value of this ratio, 1, minus three times the standard deviation (0.85), was taken as the lower limit. This ensured that paired characteristic peaks falling above this threshold were statistically attributable to the copper site signal with a confidence level of three times the standard deviation. Paired characteristic peaks with a co-location displacement ratio of not less than 0.85 are classified as copper-bismuth co-location characteristic peaks. This threshold, 0.85, is shared with the copper site characteristic peak criterion because the denominator of the co-location displacement ratio is the theoretical displacement of the co-location, and both are defined in the same way. The standard deviation originates from the peak position fitting error during the same in-situ Raman repetition measurement process, hence the same value is used. Paired characteristic peaks with copper site displacement ratios and co-location displacement ratios not exceeding 0.15 were classified as candidate bismuth site characteristic peaks. The value of 0.15 was determined as follows: The aforementioned dual-frequency vibration calculation was performed on the vibrational mode corresponding to the pure bismuth site atom cluster model. Copper atom mass replaced the displacements not involved in this vibrational mode, and the calculated theoretical displacement approached zero. The maximum value of the ratio of the peak position random noise obtained from repeated Raman spectroscopy measurements in the same batch, 0.12, was rounded up to obtain 0.15, which served as the upper limit for determining that the vibrational mode did not contain copper atom displacement components. Paired characteristic peaks with copper site displacement ratios or co-location displacement ratios between 0.15 and 0.85 were not classified into any of the three signal categories mentioned above. They were marked as unknown signal components to be further characterized and recorded. The existence of this interval reflects that the measured data may indeed contain intermediate state signals that simultaneously contain copper atom displacement components but do not meet the criteria for pure copper or pure co-location interfaces.

[0036] For correlation coefficients not less than 0.8 obtained from correlation verification, the corresponding candidate bismuth site characteristic peaks are classified as bismuth site characteristic peaks. The value of 0.8 is taken as the lower limit of strong correlation in Pearson correlation coefficient statistics, which is the same value as the correlation verification threshold for underpotential stripping voltammetry data determined earlier. This defined value is directly used here without repeating the derivation. Candidate bismuth site characteristic peaks with correlation coefficients less than 0.8 are not classified as bismuth site characteristic peaks, but are marked as unknown signal components to be further characterized and recorded. They are combined with the unknown signal components in the aforementioned range of 0.15 to 0.85.

[0037] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

Claims

1. A method for in-situ Raman spectroscopy characterization of adsorption sites in bimetallic catalyst intermediates, characterized in that, The method includes: Using copper and bismuth atomic clusters as the matrix, copper site atomic cluster models and copper-bismuth cooperative site atomic cluster models are constructed. The copper site atomic cluster models and the copper-bismuth cooperative site atomic cluster models are subjected to dual-frequency vibration calculations under natural copper isotope mass and enriched copper isotope mass, respectively, to obtain the theoretical displacement of copper sites and the theoretical displacement of cooperative sites. A two-step electrodeposition process was performed using a natural copper salt solution and a copper-enriched isotope salt solution as electrodeposition solutions to obtain a natural isotope dendritic bimetallic electrode and an enriched isotope dendritic bimetallic electrode. The natural isotope dendritic bimetallic electrode and the enriched isotope dendritic bimetallic electrode were used for the electrocatalytic reduction of carbon dioxide to formic acid reaction. In-situ Raman spectra of the *OCHO intermediate were collected at multiple potential test points within a preset potential range, and under reaction conditions where the two electrodes were at the same potential at each potential test point, the Raman spectra were divided and the peaks were paired to obtain paired characteristic peak groups. The measured peak position difference of each paired characteristic peak in the paired characteristic peak group is analyzed by ratioing it to the theoretical displacement of the copper site and the theoretical displacement of the cooperating site, respectively, to obtain the copper site displacement ratio and the cooperating site displacement ratio; the copper site characteristic peak, the copper-bismuth cooperating site characteristic peak and the candidate bismuth site characteristic peak are obtained by dividing the copper site characteristic peak, the copper-bismuth cooperating site characteristic peak and the candidate bismuth site characteristic peak by the copper site displacement ratio and the cooperating site displacement ratio. The natural isotope dendritic bimetallic electrode was subjected to underpotential deposition stripping voltammetry to obtain underpotential stripping voltammetric data. The correlation between the characteristic peaks of the candidate bismuth sites and the underpotential stripping voltammetric data was verified to obtain the characteristic peaks of the bismuth sites. The peak area ratio of the characteristic peaks of the copper-bismuth synergistic sites at each potential test point was calculated to obtain the adsorption contribution ratio-potential curve of the copper-bismuth synergistic sites for the *OCHO intermediate.

2. The method as described in claim 1, characterized in that: The construction of the copper site cluster model and the copper-bismuth co-located site cluster model are based on the copper phase lattice constant and bismuth phase lattice constant obtained by X-ray diffraction characterization of the natural isotope dendritic bimetallic electrode, and the interface coordination number and interfacial interatomic spacing obtained by high-resolution transmission electron microscopy characterization of the copper-bismuth interface region of the natural isotope dendritic bimetallic electrode. A pure copper verification electrode is obtained by electrodeposition using a natural copper salt solution alone. The pure copper verification electrode is then subjected to in-situ Raman spectroscopy of the *OCHO intermediate under the same reaction conditions as the electrocatalytic reduction of carbon dioxide to formic acid reaction to obtain the characteristic peak positions of the pure copper verification electrode. The simulated Raman characteristic peak positions of the *OCHO intermediate obtained after structural optimization of the copper site cluster model are compared with the characteristic peak positions of the pure copper verification electrode; the difference between the two is no more than 5. Yes, the copper site atom cluster model is confirmed to be effective.

3. The method as described in claim 2, characterized in that: The number of metal atoms in both the copper site cluster model and the copper-bismuth co-located site cluster model is no less than 12; in the dual-frequency vibration calculation, the mass of the natural copper isotope is 63.55 atomic mass units, and the mass of the enriched copper isotope is 64.93 atomic mass units; the theoretical displacement of the copper site and the theoretical displacement of the co-located site are both no less than 3 times the spectral resolution of the spectrometer used for the in-situ Raman spectroscopy acquisition, and the theoretical displacement of the co-located site is less than the theoretical displacement of the copper site.

4. The method as described in claim 1, characterized in that: The two-step electrodeposition includes using copper foam as a conductive substrate, performing a first-step electrodeposition in the natural copper salt solution or the enriched copper isotope salt solution to obtain a dendritic copper framework, and then placing the dendritic copper framework in a bismuth nitrate solution for a second-step electrodeposition to obtain the natural isotope dendritic bimetallic electrode or the enriched isotope dendritic bimetallic electrode.

5. The method as described in claim 4, characterized in that: The natural isotope dendritic bimetallic electrode and the enriched isotope dendritic bimetallic electrode were characterized by scanning electron microscopy, X-ray photoelectron spectroscopy and high-resolution transmission electron microscopy. The difference in the spacing between the dendritic branches did not exceed 5%, the difference in the bismuth-copper atomic ratio on the surface did not exceed 3%, and the difference in the local interatomic spacing at the copper-bismuth interface did not exceed 1%.

6. The method as described in claim 5, characterized in that: It also includes electrodepositing the natural copper salt solution and the enriched copper isotope salt solution separately to obtain a natural isotope control copper electrode and an enriched isotope control copper electrode, wherein the difference in electrodeposition current efficiency and the difference in dendritic branch density between the two do not exceed 5%.

7. The method as described in claim 1, characterized in that: The preset potential range is -0.6 volts to -1.2 volts, relative to the reversible hydrogen electrode; the reaction conditions for the electrocatalytic reduction of carbon dioxide to formic acid are a potassium bicarbonate solution saturated with carbon dioxide; the in-situ Raman spectrum of the *OCHO intermediate was acquired at 1280 nm. to Wavenumber window and to Performed within the wavenumber window.

8. The method as described in claim 1, characterized in that: The peak division is performed using a Gaussian function for multi-component fitting; the peak pairing is based on the peak position difference being within a certain range. to The pairing condition is that the difference between the area ratio of the interval and the peak area does not exceed 10 percentage points.

9. The method as described in claim 1, characterized in that: The copper site shift ratio is not less than 0.85, and is classified as the copper site characteristic peak; the copper site shift ratio is less than 0.85, and the cooperating site shift ratio is not less than 0.85, and is classified as the copper-bismuth cooperating site characteristic peak; the copper site shift ratio is not greater than 0.15, and the cooperating site shift ratio is not greater than 0.15, and is classified as the candidate bismuth site characteristic peak; if the correlation coefficient obtained from the correlation verification is not less than 0.8, the corresponding candidate bismuth site characteristic peak is classified as the bismuth site characteristic peak.